Sosialisasi Tata Cara Peningkatan SDM Masyarakat Desa Nakau Kabupaten Bengkulu Tengah - Akmal, Samsul; Cesar , Teuku Muhammad Putra; Anggrean , Fevi (Jurnal Kewirausahaan dan Bisnis, 2023)
This study aims to analyze the effectiveness of socialization of procedures for improving the Human Resources (HR) of the Nakau Village community, Bengkulu Tengah Regency. Nakau Village is one of the rural areas that still faces challenges in improving the quality of human resources. The research method used was a mixture of quantitative and qualitative approaches. A survey was conducted by distributing questionnaires to the community of Nakau Village to measure the level of participation, understanding, and perceptions of the socialization of procedures for improving human resources. In addition, in-depth interviews were also conducted to gain a deeper understanding of the factors influencing the success of this socialization. The results show that the level of community participation in the socialization of HRD procedures is quite high, but their understanding of the importance of HRD still needs to be improved. Support from the local government and related community institutions is also still a key factor that needs to be strengthened in the implementation of this socialization. The implication of this research is the need to develop a more effective and directed socialization strategy, as well as the active role of various related parties to improve the quality of human resources of the Nakau Village community and its surrounding areas.